Emotional Exhaustion and Job Satisfaction as Sequential Mediators of Customer Incivility Impact on Turnover Intention: Socioeconomic Status as a Moderator - Laksmi Budi Rinjani; Hunik Sri Runing Sawitri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Customer incivility in the service industry has been shown to substantially contribute to high employee turnover. However, the underlying psychological mechanism involving sequential mediation, as well as the moderating role of socioeconomic status in this relationship, remains underexplored. This study investigates the sequential mediating roles of emotional exhaustion and job satisfaction in linking customer incivility to turnover intention, while examining socioeconomic status (SES) as a moderating factor. Grounded in Conservation of Resources (COR) theory, data were collected from 219 restaurant employees in Surakarta, Indonesia (with a minimum of 6 months' tenure and direct customer interaction), and analyzed using SPSS Regression and PROCESS Macro to test a comprehensive 12 hypothesis encompassing direct effects, simple mediation, sequential mediation, and moderation. The findings supported all hypotheses: customer incivility significantly increased emotional exhaustion and turnover intention while decreasing job satisfaction. Emotional exhaustion and job satisfaction were found to sequentially mediate the relationship between customer incivility and turnover intention. Additionally, SES significantly moderated this process, with lower-SES employees experiencing higher levels of emotional exhaustion. These results extend COR theory by revealing a stepwise resource depletion mechanism and identifying SES as a critical vulnerability factor. The study offers practical recommendations for proactive organizational interventions, including emotional regulation training, structured peer support, and SES-responsive wellness programs. Future research is encouraged to employ longitudinal designs across diverse service sectors to enhance the generalizability of the findings.